AB0299 The incidence rate and the management of early rheumatoid arthritis in a single centre interventional clinic. (12th June 2018) - Ješe, R.; Perdan Pirkmajer, K.; Ambrožič, A.; Gašperšič, N.; Hočevar, A.; Lestan, B.; Markez, S.; Pavić Nikolić, M.; Plešivčnik Novljan, M.; Praprotnik, S.; Rotar, Ž.; Šipek Dolničar, A.; et al.
Abstract : Background: In patients with rheumatoid arthritis (RA), early diagnosis and adherence to the treat to target recommendations (T2T) limit RA progression and improve patients' quality of life. 1 However, the implementation of T2T has always been a challenge, and real-life data are lacking. Slovenia has 40% less rheumatologists per capita than the European Union average, which makes the implementation of management guidelines even more challenging. Objectives: To determine the incidence of RA and the proportion of patients with incident RA in whom first rheumatology assessment was done within the recommended time frame. Methods: We analysed the prospectively collected data of adult patients diagnosed with RA during years 2014 to 2016 at the Rheumatology Department of the University Medical Centre Ljubljana, Slovenia. The department provides rheumatology services to a well-defined region with a population of 704.000 adult residents. Dates were recorded for inflammatory joint symptom onset, referral to rheumatologist, first rheumatologic assessment and initiation of DMARD therapy. The percentage of patients assessed by a rheumatologist and/or treated with a DMARD within 12 weeks of symptom onset and the median times for delay were then calculated. Results: Between 1 January 2014 and 31 December 2016, 341 incident cases of RA (75% females, median age 61.9 (IQR 52–75.4) years) were identified, resulting in an annual incidence rate of 16/100.000 population (in females: 23.6/100.000; in males 8.3/100.000). Most patients (78.6%) were referred to our early interventional clinic. The median time from symptom onset to consultation was 12.9 (IQR 4.4–26.1) weeks, median time from referral to consultation was 1 (IQR 1–3) day. Median DMARD treatment delay was 16.6 (IQR 8.9–33.3) weeks. Within 12 weeks of symptom onset, 161 (47.2%) new RA patients were examined by a rheumatologist and 123 (36.1%) were started on DMARD therapy. Conclusions: Our prospective data support the recent reports that uncovered a decrease in RA incidence. 2 Moreover, despite the lack of rheumatologists and the heavily protracted nationwide waiting times for first rheumatologist assessment, our early interventional clinic enables us to recognise and manage substantial percentage of RA patients within the recommended time frame. References: [1] Monti S, et al. Rheumatoid arthritis treatment: the earlier the better to prevent joint damage. RMD Open2015;1(Suppl 1):e000057. doi:10.1136/rmdopen-2015-000057 [2] Abhishek, et al. Rheumatoid arthritis is getting less frequent—results of a nationwide population-based cohort study. Rheumatology2017;56:36–744–7. Disclosure of Interest: None declared